HIV incidence in an open national cohort of men who have sex with men attending sexually transmitted infection clinics in England. Issue 9 (27th January 2017) - Desai, S; Nardone, A; Hughes, G; Delpech, V; Burns, F; Hart, G; Gill, ON
Abstract : Objectives: The aim of the study was to determine HIV incidence among men who have sex with men (MSM) who repeat test for HIV at sexually transmitted infection (STI) clinics in England, and identify associated factors. Methods: Annual HIV incidence and 95% confidence interval (CI) were calculated for a national cohort of MSM who tested HIV negative at any STI clinic in England in 2012 and had a follow‐up test within 1 year using routinely collected data. Cox regression analyses were performed to identify predictors of HIV acquisition and population attributable risk for HIV infection was calculated for predictors. Results: In 2012, 85 500 MSM not known to be HIV positive attended any STI clinic in England, and 31% tested for HIV at least twice within 1 year at the same clinic. HIV incidence was 2.0 per 100 person‐years (PY; 95% CI 1.8–2.2) among repeat testers. Incidence was higher among MSM of black ethnicity (3.2 per 100 PY) and those with a bacterial STI diagnosis at the initial attendance (3.2 per 100 PY). MSM with a previous syphilis or gonorrhoea infection were at significantly greater risk of acquiring HIV in the subsequent year [adjusted hazard ratio 4.1 (95% CI 2.0–8.3) and 2.1 (95% CI 1.4–3.2), respectively]. The predictors accounted for 37% of HIV infections. Conclusions: Annual HIV incidence among MSM attending STI clinics in England is high. Previous STIs were predictors of HIV acquisition but only accounted for one in five infections. More discriminatory behavioural predictors of HIV acquisition could provide better triaging of HIV prevention services for MSM attending STI clinics.